2022
DOI: 10.15587/1729-4061.2022.265086
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the study of liquid smoke from rice husks as a green corrosion inhibitor in mild steel under 1 M HCl

Abstract: The work provides the more comprehensive development of Liquid Smoke from Rice Husks Ash (RHA). Notably, the study focuses on the interaction between the primary molecules of inhibitor and mild steel, including thermodynamic calculation and surface treatment upon addition of inhibitor. The electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization (PP) characterization were utilized to evaluate the anticorrosion of RHA. The Raman Spectroscopy pre and post-addition of RHA’s inhibitor were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Hence, the objective of the paper is to: (i) discuss the inhibition performance of the liquid smoke of RHA on C1018 under an acidic environment; (ii) evaluate the adsorption process related to surface modification, the functional group's identification, and electronic transition; (iii) model the relationship between the electrochemical result and the growth of film thickness using deep learning to quicken the analysis related to the compatibility of the inhibitor under specific conditions. The limitations of this paper include the contribution of RHA major compounds on mild steel C1018 despite multiple derivative molecules that may appear in the FTIR and UV-Vis and have been identified [15]. Moreover, the work excludes the discussion on adsorption isotherm inhibitors since it comprises more than two major compounds.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Hence, the objective of the paper is to: (i) discuss the inhibition performance of the liquid smoke of RHA on C1018 under an acidic environment; (ii) evaluate the adsorption process related to surface modification, the functional group's identification, and electronic transition; (iii) model the relationship between the electrochemical result and the growth of film thickness using deep learning to quicken the analysis related to the compatibility of the inhibitor under specific conditions. The limitations of this paper include the contribution of RHA major compounds on mild steel C1018 despite multiple derivative molecules that may appear in the FTIR and UV-Vis and have been identified [15]. Moreover, the work excludes the discussion on adsorption isotherm inhibitors since it comprises more than two major compounds.…”
Section: Introductionmentioning
confidence: 94%
“…The inhibitor solution was prepared using the pyrolysis process, which was published in our previous work [15]. In this study, the aggressive solution of 1 M HCl was prepared from 37 percent of the analytical-grade solution (Merck.…”
Section: Preparation Of Inhibitor and Test Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Langmuir adsorption isotherm with a physical nature provided the best fit, and the thermodynamic parameters indicated the endothermic nature of the corrosion process with more organized activated complexes in the presence of lignin compounds. Kaban et al 28 investigated the anti-corrosion behaviour of liquid smoke derived from rice husk ash in a 1 M HCl solution in a separate study. The corrosion tests revealed that the inhibitor acted as a mixed-type inhibitor, achieving the optimal inhibition at 80 ppm and 323 K, displaying an impressive 99% inhibition efficiency.…”
Section: Green Corrosion Inhibition: Current Advancements and Future ...mentioning
confidence: 99%
“…The Oslo Convention against Dumping of Wastes at Sea, signed in 1972, and the Paris Convention on Marine Pollution from Land-Based Sources, signed in 1974, were combined and updated to become OSPAR on September 22, 1992. [28][29][30] The bioaccumulation, biodegradability and toxicity of chemical compounds and their effects on the environment and human health can all be evaluated using the recommendations and indices established by these commissions. The effective and lethal concentrations of a chemical compound, which are denoted as EC 50 and LC 50 , respectively, can be used to evaluate the toxicity of the compound before it is utilized as a corrosion inhibitor.…”
Section: Introductionmentioning
confidence: 99%